The role of Zionist movement towards the creation of the state of Israel (Peranan pergerakan zionist terhadap pembentukan negara Israel) - Mohd Roslan Mohd Nor, (Institut Kajian Rantau Asia Barat, 2012)
The problem of Palestine has been a subject of much debate not only among scholars but also involved world superpowers as well. As this conflict rages on, there is a need to look at the root cause of the problem which one could argue that, among others, was caused by the ambitions of Zionist Movement. This paper examines the emergence of Zionist Movement and its role in establishing the State of Israel by confiscating Palestinians‟ territory and land. Zionist controls over the territory has resulted in the expulsion of Palestinians from their homeland. This study was conducted as a library research with textual analysis on the sources of Palestine historiography. The result shows that the Zionist Movement had lobbied the world superpowers, especially Britain and United States of America, until they supported the movement and resulting in the creation of the State of Israel on the Palestinian land.